Potential Novel Biomarkers in Chronic Graft-Versus-Host Disease - Crossland, Rachel E.; Perutelli, Francesca; Bogunia-Kubik, Katarzyna; Mooney, Nuala; Milutin Gašperov, Nina; Pučić-Baković, Maja; Greinix, Hildegard; Weber, Daniela; Holler, Ernst; Pulanić, Dražen; Wolff, Daniel; Dickinson, Anne M.; et al. (Frontiers in Immunology, 2020)
Prognostic, diagnostic or predictive biomarkers are urgently needed for assessment of chronic graft-versus-host disease (cGvHD), a major risk for patients undergoing allogeneic hematopoietic stem cell transplantation. The main goal of this review generated within the COST Action EUROGRAFT “Integrated European Network on Chronic Graft Versus Host Disease” was to identify potential novel biomarkers for cGvHD besides the widely accepted molecular and cellular biomarkers. Thus, the focus was on cellular biomarkers, alloantibodies, glycomics, endothelial derived particles, extracellular vesicles, microbiome, epigenetic and neurologic changes in cGvHD patients. Both host-reactive antibodies in general, and particularly alloantibodies have been associated with cGvHD and require further consideration. Glycans attached to IgG modulate its activity and represent a promising predictive and/or stratification biomarker for cGVHD. Furthermore, epigenetic changes such as microRNAs and DNA methylation represent potential biomarkers for monitoring cGvHD patients and novel targets for developing new treatment approaches. Finally, the microbiome likely affects the pathophysiology of cGvHD; bacterial strains as well as microbial metabolites could display potential biomarkers for dysbiosis and risk for the development of cGvHD. In summary, although there are no validated biomarkers currently available for clinical use to better inform on the diagnosis, prognosis or prediction of outcome for cGvHD, many novel sources of potential markers have shown promise and warrant further investigation using well characterised, multi-centre patient cohorts.